Rational Choice Approach on Ramadan Activity: A Conceptual Study - Riyardi, Agung; Romdhoni, Abdul Haris; Syahputra, Faturrochman; Insyarah, Dwi Arum Nur (Jurnal Ilmiah Ekonomi Islam, 2024)
Muslims conduct more and harder worship during Ramadan than non-Ramadan. Studies show positive effects indicating Ramadan hard worship as rational. However, no studies discuss Ramadan worship based on the rational choice approach although this approach can reveal what, why, and how a decision is rational. Based on the rational choice approach, this study aims to demonstrate graphically Ramadan worship and general activity combination, relative price, constraint, and equilibrium. This paper employs the rational choice graphical modelling that consists of the Ramadan worship indifference curve graphing, relative price setting, constraint line graphing, and equilibrium graphing. Four results are found. Firstly, the worship indifference curves reveal that worship perfectly complements to general activity. Secondly, the worship relative price decreases from non-Ramadan to Ramadan. Thirdly, the worship constraint lines rotate up caused by decreasing worship relative price. Fourthly, the Ramadan equilibrium demonstrates that Muslim is satisfied by a relative price-decreasing-caused Ramadan hard worship that exploits physical capability but without general activity interfering